A estrutura de semigrupos numéricos esparsos - Burock, Katherine Pereira (2017)
Sparse semigroups will be studied in this dissertation by analyzing their classifications and properties, such as their upper limits for the genus, the interaction between the single and double leaps, the influence of the genus on the leaps, the influence of the parity of the Frobenius number and also the classification of limit sparse semigroups. At the end we will give an introduction to ?-sparse semigroups by analyzing their structure and trying to extend some notions and properties as a natural generalization of the sparse semigroups. For this we will review other published works on the subject, where the main reference used was [1] “On the structure of numerical sparse semigroups and applications”